Teacher codeswitching in a communicative EFL context : measuring effects on vocabulary learning - Tian, L (2009)
This study is focused on exploring the possible impact of the teacher’s use of codeswitching on learners’ second language vocabulary learning and judicious use of the mother tongue in second language classroom. Previous studies attempted to observe classroom codeswitching or hypothesize theoretically the possible effect of codeswitching on second language learning, rather than empirically testing its effects. While most studies examining classroom codeswitching behaviors indicate a wide range of teacher L1 use, one of the most important functions of L1 is to clarify the meaning of unfamiliar lexical items. A brief review indicates a clear gap in the literature on the exploration of the link between vocabulary learning, listening comprehension, meaning negotiation and form-focused instruction. In this way this study attempts to fill the gap by examining the role of codeswitching in vocabulary learning when learners are presented with listening materials and encouraged to interact with the teacher and negotiate meaning of the listening materials and new vocabulary without disrupting the communicative orientation of the lessons. One hundred and seventeen first-year English-majors in a Chinese university were randomly assigned into three groups: the codeswitching group, in which codeswitching was used by the teacher to explain English vocabulary, that is, the teacher provided Chinese equivalents for the English target words, the non-codeswitching group, which received lessons without the teacher’s switching to Chinese, in other words, the teacher provided English information for the English target words; and a control group. During the two-month experiment, vocabulary and listening comprehension scores on pretests, immediate posttests and a delayed posttest were collected and analyzed statistically. Lexical episodes of the teacher-students interactions were collected through classroom observation. Thus, a mixed method research design was employed in this study. Results show that it is in fact beneficial to focus on form on lexical items in a communicative language classroom. The students’ vocabulary learning was better facilitated by the teacher’s use of codeswitching for short term learning. However, this advantage disappeared when long term learning was considered. Further analysis shows the students with the lowest prior lexical knowledge and who have difficulties in understanding the listening passages benefited most from the teacher’s codeswitching use in the short term, but the students with the highest prior lexical knowledge retained more words from the teacher’s provision of L2 information in the long term. Qualitative analysis of the teacher’s lexical input and the students’ reactions during the lexical episodes of the teacher-students interactions supports the above results and provides further insights into the teacher’s decision-making.